Fiscal Deficit and Public Debt in the Western Balkans : 15 Years of Economic Transition - Koczan, Zsoka (Washington, D.C. : International Monetary Fund, 2015)
In this paper we analyze how Western Balkans public finances adapted to the boom-bust cycle. Large capital inflows into emerging European economies during the mid-2000s resulted in rapid economic growth and convergence to EU income levels. This also resulted in improved fiscal positions of most countries, on the back of strong revenue performance. Yet, since the onset of the global economic crisis, many countries have struggled to adjust to the new situation of lower external financing and lower growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet